2008
DOI: 10.1097/pas.0b013e3181753a8e
|View full text |Cite
|
Sign up to set email alerts
|

Angiotropism is an Independent Predictor of Local Recurrence and In-transit Metastasis in Primary Cutaneous Melanoma

Abstract: The migration of melanoma cells along the external surface of blood vessels (angiotropism) has recently been proposed as a mechanism for melanoma metastasis (termed extravascular migratory metastasis). To determine whether the presence of angiotropism, as seen in the routine hematoxylin and eosin sections of primary cutaneous melanomas (PCMs), predicts the development of local or in-transit melanoma recurrence, 32 patients with a PCM who developed local or in-transit recurrence were matched for Breslow thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 26 publications
3
42
1
Order By: Relevance
“…The detection of angiotropism within a primary melanoma may have an impact on the planning of surgical margins. 10 Furthermore, understanding the underlying molecular mechanisms of intravascular dissemination and EVMM, and the relationship between these processes, may also have therapeutic implications for melanoma patients.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of angiotropism within a primary melanoma may have an impact on the planning of surgical margins. 10 Furthermore, understanding the underlying molecular mechanisms of intravascular dissemination and EVMM, and the relationship between these processes, may also have therapeutic implications for melanoma patients.…”
Section: Resultsmentioning
confidence: 99%
“…12 A more recent case-control study examined only patients with recurrent melanoma (local metastases) or in-transit metastases; angiotropism strongly correlated with the latter end points. 13 In an important general mechanistic sense, there is increasing experimental evidence that the molecular basis of such tumor cell migration is closely linked to the developmental biology of the neural crest (NC), that is, the migration of NC stem cells from the NC in the embryo. 2 Therefore, a better understanding of such mechanisms of cellular migration may be fundamental not only to melanoma metastasis but also as a means of explaining the migration of melanocytes in general and in other melanocytic neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…During EVMM, angiotropic MC migrate along the abluminal surfaces of vessels in a pericytic location, without intravasation, recapitulating embryonic migration in order to reach secondary sites [4]. Interestingly, angiotropism has been shown to be a prognostic factor for melanoma metastasis [4][5][6], as well as a microscopic marker of EVMM in in vitro and in vivo experiments [4,[7][8][9]. Furthermore, a recent study has demonstrated the perivascular localization of malignant tumor cells along the celiac trunk in patients with pancreatic carcinoma, consistent with EVMM [10].…”
Section: Introductionmentioning
confidence: 99%